Fabrication of a Spherical Superstructure of Carbon Nanorods. Issue 24 (29th April 2019) - Zou, Lianli; Kitta, Mitsunori; Hong, Jinhua; Suenaga, Kazutomo; Tsumori, Nobuko; Liu, Zheng; Xu, Qiang
Abstract: Hierarchical superstructures in nano/microsize have attracted great attention owing to their wide potential applications. Herein, a self‐templated strategy is presented for the synthesis of a spherical superstructure of carbon nanorods (SS‐CNR) in micrometers through the morphology‐preserved thermal transformation of a spherical superstructure of metal–organic framework nanorods (SS‐MOFNR). The self‐ordered SS‐MOFNR with a chestnut‐shell‐like superstructure composed of 1D MOF nanorods on the shell is synthesized by a hydrothermal transformation process from crystalline MOF nanoparticles. After carbonization in argon, the hierarchical SS‐MOFNR transforms into SS‐CNR, which preserves the original chestnut‐shell‐like superstructure with 1D porous carbon nanorods on the shell. Taking the advantage of this functional superstructure, SS‐CNR immobilized with ultrafine palladium (Pd) nanoparticles (Pd@SS‐CNR) exhibits excellent catalytic activity for formic acid dehydrogenation. This synthetic strategy provides a facile method to synthesize uniform spherical superstructures constructed from 1D MOF nanorods or carbon nanorods for applications in catalysis and energy storage. Abstract : Fabrication of 3D spherical superstructures composed of 1D nanorods is a challenge. A 3D chestnut‐shell‐like superstructure assembled by 1D metal–organic framework (MOF) nanorods is synthesized via the hydrothermal transformation of MOF nanoparticles, which are carbonized to a spherical superstructure of carbon nanorods (SS‐CNR). The SS‐CNR shows excellent performance for immobilizing Pd nanoparticles with high catalytic activity for formic acid dehydrogenation.